ANALISIS KEMAMPUAN TPACK GURU KIMIA DI KUANTAN SINGINGI DAN KOTA PEKANBARU - Amlen Sutrisno; Jimmi Copriady; Lenny Anwar (Universitas Riau, 2023)
The research results are presented based on gender, certification status, work location, and work years. Based on gender, male teachers have slightly better TPACK abilities than female teachers. Based on certification status, the TPACK ability of certified teachers is better than teachers who are not certified. Based on work location, teachers in Pekanbaru City are better than teachers in Kuantan Singingi Regency. Based on years of service, teachers with 20 years of service are teachers who have very good TPACK abilities.